That summer - Willig, Lauren (New York : St. Martin's Press, 2014)
Julia Conley has inherited a house outside London from an unknown great-aunt, but she hasn't been in England since a car crash killed her mother when she was six, an event she remembers only in her nightmares. When she begins sorting through the house bits of memory start coming back.
Keywords: Inheritance and succession -- Fiction; Antique dealers -- England -- Fiction; Love stories; Historical fiction